Factors associated with unmet needs in individuals with schizophrenia in Chile - Rubén Alvarado; Francisco Torres González; Sara Schilling; Francisca Alvarado; Carlos Domínguez; Berta Moreno Küstner; Francisco Aliste (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2012)
OBJECTIVE: To evaluate the possible associations between different sociodemographic, clinical, and healthcare factors and the number of unmet needs among people being treated for schizophrenia. METHODS: The sample was made up of 141 subjects who were being treated at eight mental health service networks throughout Chile. Unmet need was assessed with the Camberwell Assessment of Need, which was specifically created for people with severe mental disorders. A multiple linear regression analysis was also applied. RESULTS: It was found a direct association with clinical variables: score in the Positive and Negative Syndrome Scale, global functioning at diagnosis, and change in global functioning at diagnosis from diagnosis to interview. However, sociodemographic (ethnicity, education level, and number of people who live with subject) and other clinical variables (age at diagnosis, and annual rate of relapse) were indirectly associated with unmet needs. CONCLUSIONS: Our results can be applied in order to coordinate and improve the effectiveness of mental health services in Chile.